Pilotní studie: korekce levátorového hiátu anální páskou jako chirurgická metoda léčby střevní inkontinence - Ducháč, V; Otčenášek, M; Skrabalová, D; Lukáš, D; Gürlich, R (Rozhledy v chirurgii, 2014)
INTRODUCTION: Faecal incontinence is a significantly depressing and mentally devastating disability. Surgical treatment, as a first choice method, is indicated for incontinence originating as a result of traumatic or iatrogenic infliction of the sphincter apparatus, particularly of the external sphincter. In case of idiopathic (neurogenic) incontinence, it is indicated very exceptionally, if ever. The authors present a pilot study to verify the possibility of surgical treatment of anal incontinence with the support of a puborectal muscle loop by means of the absorbable STRATASIS® TF mesh. MATERIAL AND METHODS: In the years 2010-2012, eight experimental surgical procedures were performed. Female patients with a history of faecal incontinence of the third stage longer than one year and with EMG-verified neurological lesion were recruited. The evaluating criteria were the Wexner score and changes in the levator and anorectal angle acquired from a MR defecographic examination performed before and six months after the operation. RESULTS: The complaints improved distinctly in six patients; in the two remaining cases, the method failed completely. The failures were associated with an inflammatory complication in both cases. In one patient, the authors do not rule out an incorrect indication, too. The Wexner score decreased from 18 to 10 in improved patients. Changes in the levator and anorectal angle were not significant. CONCLUSION: The results confirm the possibility of successful surgical influence on incontinence of the third stage by correcting the levator hiatus with biodegradable mesh. Continence improvement persists even after the mesh transforms into scar tissue.
Keywords: senioři; Middle Aged; Surgical Mesh; Adult; chirurgické síťky; fekální inkontinence; anální kanál; ženské pohlaví; Humans; elektromyografie; Electromyography; pilotní projekty; lidé středního věku; Pilot Projects; Fecal Incontinence; dospělí; Anal Canal; Female; Aged; lidé